To the Issue of the Practice Theory Development - N. K. Tchapayev; A. V. Yefanova (Russian State Vocational Pedagogical University, 2015)
The paper deals with the theoretical analysis of practical training as one of the two main forms of vocational training. Industrial practice is regarded as poly-systematic, alternative existence of students entering the adults' world, the means for developing students' functional responsibility and subjective world outlook, etc. The paper overcomes the existing utilitarian one-sided approach to the place and value of practice, its impact on the specialist's professional development and opportunities for professional growth being explored. Regarding the practical training as psycho-pedagogical and educational phenomenon, the authors developed the theoretical and methodological bases for its designing and conducting in vocational schools. The research conclu- sions contain some heuristic innovative potential facilitating both the foundation of independent theory of practical training and organization of practice oriented training in vocational schools.